A case of Candida auris candidemia in Xiamen, China, and a comparative analysis of clinical isolates in China. Issue 1 (2nd January 2022) - Bing, Jian; Wang, Sijia; Xu, Heping; Fan, Shuru; Du, Han; Nobile, Clarissa J.; Huang, Guanghua
ABSTRACT: The recently emerged fungal pathogen Candida auris often displays resistance to one or more antifungal drugs. Its infections have been identified in at least 40 countries on six continents to date. Here we report a case of C. auris candidemia in a patient in Xiamen, a city in south China. We also review currently reported cases of C. auris infection in China and compare the genetic and biological features of C. auris strains isolated from this country. Our phylogenetic analysis indicates that there are at least two C. auris genetic clades present in China (the South African clade and the south Asian clade) that display opposite mating type loci (one is MTL a and the other is MTL α). We also found that there are several distinct features among the clinical isolates studied, including the expression of virulence factors, antifungal susceptibilities, and cellular morphologies, and that these features could be associated with the mating-type of the isolate. For example, C. auris MTL a isolates generally secreted higher levels of secreted aspartyl proteases (Saps) at ambient environmental temperatures. Taken together, this study demonstrates that C. auris clinical isolates from China exhibit diversity in both biological and genetic features.